Bis(acetato-κ2O,O′)(2,2′:6′,2′′-terpyridine-κ3N,N′,N′′)manganese(II) dihydrate - Kwang Ha (Acta Crystallographica Section E, 2012)
The MnII ion in the title compound, [Mn(CH3CO2)2(C15H11N3)]·2H2O, is seven-coordinated in a considerably distorted pentagonal–bipyramidal geometry by three N atoms of the tridentate 2,2′:6′,2′′-terpyridine ligand and four O atoms from two acetate anions which chelate the Mn atom via two O atoms. The lateral pyridine rings are slightly inclined to the central pyridine ring, making dihedral angles of 13.6 (2) and 5.7 (2)°. The complex and solvent water molecules are linked by intermolecular O—H...O hydrogen bonds into a three-dimensional network.